Erucic acid derived from rosemary regulates differentiation of mesenchymal stem cells into osteoblasts/adipocytes via suppression of peroxisome proliferator‐activated receptor γ transcriptional activity. (27th January 2020) - Takahashi, Asako; Dohi, Hirofumi; Egashira, Yukari; Hirai, Shizuka
Abstract : Osteoporosis is associated with increase in fat tissue in bone marrow in humans. Mesenchymal stem cells in bone marrow are induced to differentiate into osteoblasts rather than adipocytes by the stimulation of peroxisome proliferator‐activated receptor (PPAR) γ antagonists. PPARγ antagonists are expected to be useful to prevent osteoporosis by regulating the lineages of mesenchymal stem cells in bone marrow, as well as the prevention of obesity. In this study, we explored natural components suppressing PPARγ transcriptional activity in rosemary. Separation of active fraction of rosemary extract by repeated high performance liquid chromatograph and PPARγ luciferase reporter assay identified erucic acid, one of the monounsaturated fatty acids, as an active component. Twenty‐five‐micrometer erucic acid significantly decreased PPARγ luciferase activity and enhanced the differentiation of mouse‐delivered C3H10T1/2 cells into osteoblasts rather than adipocytes. Furthermore, 25‐μM erucic acid significantly decreased the expression of adipocyte marker genes, while accelerating osteoblast marker genes. In conclusion, erucic acid is a novel natural component derived from rosemary regulating mesenchymal stem cell differentiation via suppression of PPARγ transcriptional activity.